Rekonstruksi Integritas Panggilan Pelayanan Melalui Kajian Hermeneutik Injil Lukas 23:50-56a - Annatasya Tanti Meilynda Worang; Peggy Sandra Tewu (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2025)
The church is called to serve with integrity, but is often faced with ethical and moral challenges that threaten the credibility of its ministry. Often the church is used as a means of power, with church leaders preferring to compromise with corrupt systems for the sake of position and a comfortable life rather than upholding faith and truth. This points to a deep crisis of integrity in ministry. This study aims to reconstruct the understanding of integrity in ministry through a hermeneutical analysis of the narrative in Luke 23:50-56a, which focuses on the figure of Joseph of Arimathea. As a member of the Sanhedrin, Joseph was faced with a difficult choice: to prioritize his position or to act out of compassion for Jesus. He chose to take down and bury Jesus' body, an act that went against the Sanhedrin's consensus and could potentially endanger himself. This study uses a qualitative approach, with narrative hermeneutics based on E. G. Singgih's method, which includes: structure, plot, characters, conflict, setting, time, style, and narrator. The results of the study show that integrity in service lies not only in institutional obedience, but in the willingness to transcend institutional and social barriers. Joseph's actions show that true service is rooted in moral courage and compassion, which are capable of setting aside personal, political, and comfort interests. Contemporary churches must reconstruct their understanding of ministry to emphasize courage, ethics, and commitment, even when facing personal risk. In this way, the ministry of the Church can once again become an authentic and transformative witness.